2007
DOI: 10.1093/humrep/dem261
|View full text |Cite
|
Sign up to set email alerts
|

Matched follow-up study of 5 8-year-old ICSI singletons: child behaviour, parenting stress and child (health-related) quality of life

Abstract: Prevalence of autism/ASD seemed higher after ICSI, but this unexpected finding should be confirmed by future studies with larger group sizes. ICSI parents experienced more stress than NC parents, although selection bias cannot be ruled out. The majority of ICSI singletons assessed at age 5-8 years showed a normal psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 39 publications
4
56
0
3
Order By: Relevance
“…No differences were found according to family type for children's positive or negative feelings toward, or involvement with, either their mothers or their fathers. Similar findings were reported from a study in the Netherlands of ICSI families, IVF families, and natural conception families with 5-to 8-year-old children (Knoester, Helmerhorst, van der Westerlaken, Walther, & Veen, 2007). In a study of 8-year-olds in Belgium (Leunens, Celestin-Westreich, Bonduelle, Liebaers, & Ponjaert-Kristoffersen, 2006), there were no differences in the parenting stress reported by mothers and fathers.…”
Section: Parenting In Icsi Familiessupporting
confidence: 86%
See 1 more Smart Citation
“…No differences were found according to family type for children's positive or negative feelings toward, or involvement with, either their mothers or their fathers. Similar findings were reported from a study in the Netherlands of ICSI families, IVF families, and natural conception families with 5-to 8-year-old children (Knoester, Helmerhorst, van der Westerlaken, Walther, & Veen, 2007). In a study of 8-year-olds in Belgium (Leunens, Celestin-Westreich, Bonduelle, Liebaers, & Ponjaert-Kristoffersen, 2006), there were no differences in the parenting stress reported by mothers and fathers.…”
Section: Parenting In Icsi Familiessupporting
confidence: 86%
“…The CBCL was also administered to mothers by Knoester et al (2007). Although no differences were identified between ICSI, IVF and naturally conceived boys, there was a difference found between ICSI and IVF girls, resulting from the particularly low scores of IVF girls.…”
Section: Children In Icsi Familiesmentioning
confidence: 99%
“…No significant differences were found between the ICSI and IVF groups for communication, self-dependence, locomotion, work skills, socialization, or self-management. A publication by Knoester et al (2007) also showed that child behaviors are comparable after ICSI, IVF, and natural conception. However, the prevalence of autism/autism spectrum disorders (ASDs) seemed higher after ICSI (Knoester et al, 2007).…”
Section: Psychosocial Developmentmentioning
confidence: 97%
“…6,7 The physical, neurological, and developmental health of children born after ART has been examined in many epidemiological studies, with contradictory results. Most small studies reported no effect, [24][25][26][27][28][29][30][31] whereas the larger studies have found an increased risk of developmental delay. [32][33][34][35] A recent systematic review and meta-analysis has also addressed the question of developmental delay in children born after ART.…”
Section: Estradiol (Nmol/l)mentioning
confidence: 99%